Effect of sandblasted large grit acid etching and ultraviolet-c photofunctionalization of titanium on osteoblast cell viability: an in vitro study - Tjandra, Andreas; Murdiastuti, Kwartarini; Kusumaatmaja, Ahmad; Susilowati, Heni (Padjadjaran Journal of Dentistry, 2026)
Introduction: Sandblasted Large Grit Acid Etching (SLA) is a widely used titanium implant surface modification technique that enhances osseointegration. Ultraviolet C (UV-C) photofunctionalization is a method that modifies the physicochemical properties of titanium surfaces by removing hydrocarbon contaminants and increasing hydrophilicity. However, the combined effects of these modification techniques on MC3T3-E1 osteoblast cell viability require further investigation. Therefore, this study aimed to analyze the effect of SLA treatment and its interaction with UV-C irradiation on MC3T3-E1 osteoblast cell viability on titanium disks. Methods: This in vitro experimental study used titanium disks (10 mm in diameter and 1 mm in thickness), which were divided into SLA-treated and non-SLA groups. Each group was further subdivided according to UV-C irradiation (90 W, 254 nm) into four subgroups: non-UV (control), 10 minutes, 30 minutes, and 48 hours (n = 4 per subgroup). MC3T3-E1 osteoblasts (1.2×104 cells/well) were seeded onto disk surfaces and cultured for 24 hours. Cell viability was assessed using the MTT assay. Data normality was evaluated using the Shapiro-Wilk test, homogeneity using the Brown-Forsythe test, and differences between groups using two-way ANOVA, with statistical significance set at p <0.05. Results: Two-way ANOVA revealed that UV irradiation had no significant effect on cell viability (F=2.388; p=0.093). Similarly, SLA treatment showed no significant effect (F= 1.679; p = 0.207), and no significant interaction was observed between SLA treatment and UV-C irradiation (F=0.041; p=0.988). The highest mean cell viability was observed in the non-SLA group exposed to UV-C irradiation for 10 minutes (88.53 ± 25.22), whereas the lowest mean cell viability was found in the SLA group without UV-C irradiation (45.55 ± 16.29). Conclusion: Neither UV-C irradiation nor SLA treatment significantly affected MC3T3-E1 osteoblast cell viability, and no significant interaction was observed between the two treatments.